The shear strength of soft clay reinforced with single and group crushed brick column - Muzamir, Hasan; Wei, O. C.; Ler, L. Y.; Pahrol, F. -H; Hyodo, M. (IOP Publishing, 2020)
Soft Clay is often known to be a problematic soils in construction because of its low strength and high compressibility characteristic. Before construction begins, ground improvement needs to be done to improve the soil bearing capacity so that the superstructure can be placed on top of it and reduce settlement and consolidation. In this study, the soft clay is going to be reinforced with crushed brick column which is part of construction waste produced during construction stage to achieve sustainable construction. This study was aimed to investigate the effectiveness of single and group crushed brick column in improving the shear strength by using laboratory scale model. Kaolin is being used as soil sample while crushed brick as the reinforced column. Few laboratory tests are conducted to determine the properties of kaolin clay and crushed brick. Unconfined Compression Test (UCT) also used to test the shear strength of the reinforced kaolin samples The improvement of shear strength of single crushed brick column with area replacement ratio of 4.00% (10mm column diameter) are 3.34%, 4.60% and 1.07% at sample penetration ratio, Hc/Hs of 0.6, 0.8 and 1.0 respectively while for area replacement of 10.24% (16 mm column diameter) are 7.56%, %, 16.37% and 4.97% at the same penetration ratio.. The result shows that the improvement shear strength for height penetration ratio of 1.0 is 13.33% which was the highest, while 0.6 and 0.8 are 12.31% and 9.79% respectively for group crushed brick columns with diameter 10mm. The improvement of shear strength is highest for height penetration ratio of 1.0 with 16.10% improvement which was slightly higher than 0.6 and 0.8 which were 13.49% and 11.35% respectively in sample reinforced with grouped columns with diameter 16mm. It can be concluded that the shear strength of soft clay could be improved by installation of single and group crushed brick column.